The lamp is lit : leaves from a journal - Bond, Ruskin (New Delhi, India ; New York, USA : Penguin Books, 1998)
Autobiographical.
Keywords: Bond, Ruskin; Authors, English -- 20th century -- Biography; British -- India -- Biography